Semantic view on the composite and decorative features of the landscape object - Zajkova, E Ju (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii︠a︡ agronomii︠a︡ i zhivotnovodstvo, 2015)
In article problems of an art and sign assessment of quality of the surrounding landscape environment and objects of landscape architecture are considered. Volume and spatial characteristics of an image of landscape object promote visual determination of volumes and characteristic features of the elementary forms filling them structures in color, brightness, the movement, a sign, contrast, nuance, etc. Using of semantic signs in the creation of identical model of space means of landscape design assumes integrity of an image of landscape object with decorative and art characteristics. The choice of spatial signs stretches from early experiments of the end of the 30th years of the last century with plasticity of a relief and natural materials up to now and ecological design with soft integration of the project into a landscape of this climatic zone at the principles of nuance and identity. In article it will be a question of development of new typological bases of design of landscape objects on the basis of the subject “Silhouette and Plasticity”.